Hemostatic Challenges in Pediatric Critical Care Medicine—Hemostatic Balance in VAD - Ghbeis, Muhammad Bakr; Vander Pluym, Christina J.; Thiagarajan, Ravi Ram (Frontiers in Pediatrics, 2021)
Ventricular assist devices (VAD) are used more in children. Safe and effective anticoagulation is required for successful management of children supported with ventricular assist devices. Developmental hemostasis, device hemocompatibility, plastic to body ratio, surgical variable techniques, lack of knowledge on pharmacokinetics of anticoagulants, and wide variability in anticoagulation protocols have all contributed to increased incidence of bleeding and thromboembolic complications. New collaborative learning networks, such as the ACTION network, provide opportunities to define best practices, optimize, and reduce anticoagulation related adverse events. ACTION was established Dec 2017. It consists of expert clinicians in heart failure, as well as researchers, parents, and patients, with goals to improve outcomes, share data, improve education and standard practice for children with heart failure (1, n.d). Changes in pediatric VAD anticoagulation strategy from using mainly heparin to DTI such as bivalirudin have helped reduce bleeding and clotting complications.